PENGARUH KREATIVITAS KERJA, MOTIVASI KERJA DAN KOMUNIKASI EFEKTIF TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT SIMEULUE CUT KABUPATEN SIMEULUE - muhammad muhammad; Banta Karollah (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2022)
This study aims to determine the effect of work creativity, work motivation and effective communication on employee performance at the Simeulue sub-district office. The sample of this study was set at 37 respondents. This result in a partial test shows that work creativity has an effect on employee performance by 0.224 or 22.4%. Likewise, work motivation has an effect on employee performance by 0.636 or 63.6%. Thus, effective communication affects employee performance 0.236 or 23.6%. After the T test shows that: 1. Work creativity affects employee performance Tcount 1.898> Ttable 1.690 and p value 0.004 < from p 0.05 means significant. 2. Work motivation has an effect on employee performance. Tcount 4,459 > ​​Ttable 1,690 with p value 0.000 from < 0.05 meaning significant. 3. Effective communication has an effect on employee performance. Tcount 2.706 > Ttable 1.690 with p value 0.003 from <0.05 meaning significant. Simultaneously there is an influence between work creativity, work motivation, effective communication and employee performance of 0.741 or 74.1% and 0.259 or 25.9% is influenced by other variables. After the F test, the Fcount > Ftable or (31.432> 3.28) and the significant test that the p value of 0.000 < p which was set at 0.05 or (0.000 <0.05) which means significant.